1981
DOI: 10.1159/000232714
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Immunoregulation of Antibody Response in Normal and Autoimmune Mice Is Mediated by Suppressor T Cell Subsets

Abstract: The mechanism through which interferon exerts immunoregulatory influence on antibody production in autoimmune NZB mice and normal Balb/C mice was studied. Interferon suppressed T cell-dependent anti-SRBC response in normal mice indirectly by activating suppressor T cells. The suppressor cell activity induced by interferon is mediated by Ly123+ cells presumably acting as feedback regulators for the suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…IFN and IL2 seem to exert a major role in immunoregulation (Gillis and Watson, 1980;Johnson and Blalock, 1980;Kadish et al, 1980;Attallah et al, 1981;Ruscetti and Gallo, 1981;Nair and Schwartz, 1983). IFN and IL2 augment NK activity both in vitro and in vivo (Herberman et al, 1979;Henny et al, 1981;Perussia and Trinchieri, 1981;Nair and Schwartz, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…IFN and IL2 seem to exert a major role in immunoregulation (Gillis and Watson, 1980;Johnson and Blalock, 1980;Kadish et al, 1980;Attallah et al, 1981;Ruscetti and Gallo, 1981;Nair and Schwartz, 1983). IFN and IL2 augment NK activity both in vitro and in vivo (Herberman et al, 1979;Henny et al, 1981;Perussia and Trinchieri, 1981;Nair and Schwartz, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study on the NZB model of SLE, we found that mouse IFN significantly enhanced Ig pro duction at concentrations as low as 250 IFN u/culture [24]. In another study on normal human poly clonal Ig production, lymphoblastoid IFN was found to suppress normal polyclonal Ig synthesis in a doserelated manner [11], Others have noted enhancement of in vitro human Ig biosynthesis by IFN-a and these differences appear to result, at least in part, from var ied culture conditions and IFN-a preparations used [11,25,26].…”
Section: Discussionmentioning
confidence: 79%